Influence of potassium fertilization on the functional components and antioxidant activity of pummelo [Citrus maxima (Burm. Ex Rumph.) Merr.] fruit - Magbalot-Fernandez, Alminda; De Guzman, Constancio C. (Annals of Tropical Research, 2022)
This study aimed to determine the influence of potassium (K) fertilization on the functional components and antioxidant activity of 13-year-old ‘Magallanes’ pummelo [Citrus maxima (Burm. Ex Rumph.) Merr.]. The field experiment was conducted at South Davao Corporation (SODACO) farm, Davao City for 12-month duration. Five treatments with increasing K levels were applied per tree: control, no K, 150g K basal, 225g K basal, and 225g K basal + foliar application. The functional components and antioxidant activity were analyzed following harvest at the University of the Philippines, Los Baños. Application of 225g K rates positively influenced functional components of pummelo. The yield of total phenol, flavonoid, vitamin C and oil per tree increased by 3-10 times with 225g K application. The effects of basal alone and foliar + basal application of K were only significantly different from each other in terms of flavonoid yield per tree. On the other hand, the application of 225g K basal + foliar resulted to higher total phenol, vitamin C and oil yield per tree in pummelo, implying a higher mobilization of K in the leaves than K uptake by the roots. The results of the study indicated the important role of K in improving the functional components in ‘Magallanes’ pummelo.